Asteroseismology of hybrid δ Scuti-γ Doradus pulsating stars - Sánchez Arias, Julieta Paz (2017)
Context. Hybrid δ Scuti-γ Doradus pulsating stars show acoustic (p) oscillation modes typical of δ Scuti variable stars, and gravity (g) pulsation modes characteristic of γ Doradus variable stars simultaneously excited. Observations from space missions such as MOST, CoRoT, and Kepler have revealed a large number of hybrid δ Scuti-γ Doradus pulsators, thus paving the way for an exciting new channel of asteroseismic studies. Aims. We perform detailed asteroseismological modelling of five hybrid δ Scuti-γ Doradus stars. Methods. A grid-based modeling approach was employed to sound the internal structure of the target stars using stellar models ranging from the zero-age main sequence to the terminal-age main sequence, varying parameters such as stellar mass, effective temperature, metallicity and core overshooting. Their adiabatic radial (ℓ = 0) and non-radial (ℓ = 1,2,3) p and g mode periods were computed. Two model-fitting procedures were used to search for asteroseismological models that best reproduce the observed pulsation spectra of each target star. Results. We derive the fundamental parameters and the evolutionary status of five hybrid δ Scuti-γ Doradus variable stars recently observed by the CoRoT and Kepler space missions: CoRoT 105733033, CoRoT 100866999, KIC 11145123, KIC 9244992, and HD 49434. The asteroseismological model for each star results from different criteria of model selection, in which we take full advantage of the richness of periods that characterises the pulsation spectra for this kind of star.